2014
DOI: 10.1126/science.1253714
|View full text |Cite
|
Sign up to set email alerts
|

Rabbit genome analysis reveals a polygenic basis for phenotypic change during domestication

Abstract: The genetic changes underlying the initial steps of animal domestication are still poorly understood. We generated a high-quality reference genome for rabbit and compared it to resequencing data from populations of wild and domestic rabbits. We identified over 100 selective sweeps specific to domestic rabbits, but only a relatively small number of fixed (or nearly fixed) SNPs for derived alleles. SNPs with marked allele frequency differences between wild and domestic rabbits were enriched for conserved non-cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
399
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 357 publications
(444 citation statements)
references
References 75 publications
33
399
0
12
Order By: Relevance
“…This finding is not a surprise and is consistent with the rapid evolution of genes in the nervous systems of other domestic animals, which has collectively been attributable to behavioral shifts that accompany domestication [14][15][16][17][18]. In addition, functional enrichment analysis of genes in regions with the top 1% XP-EHH scores revealed that many candidate genes related to the npg www.cell-research.com | Cell Research nervous system were over-represented in the following Human Phenotype Ontology (HPO) categories: abnormality of the nervous system (31 genes), abnormality of the central nervous system (30 genes), and cognitive impairment (25 genes) (P < 0.05) (Supplementary information, Table S8).…”
Section: Positively Selected Genes In Domestic Chickens Compared Withsupporting
confidence: 68%
“…This finding is not a surprise and is consistent with the rapid evolution of genes in the nervous systems of other domestic animals, which has collectively been attributable to behavioral shifts that accompany domestication [14][15][16][17][18]. In addition, functional enrichment analysis of genes in regions with the top 1% XP-EHH scores revealed that many candidate genes related to the npg www.cell-research.com | Cell Research nervous system were over-represented in the following Human Phenotype Ontology (HPO) categories: abnormality of the nervous system (31 genes), abnormality of the central nervous system (30 genes), and cognitive impairment (25 genes) (P < 0.05) (Supplementary information, Table S8).…”
Section: Positively Selected Genes In Domestic Chickens Compared Withsupporting
confidence: 68%
“…Similar developments happens in species that have been domesticated at different historical time periods and in different parts of the world. For example, the dog was the first domesticated species, originating in south-east Asia some 15000 years ago (Ding et al, 2011), and the rabbit is a late addition domesticated about 1400 years ago in southern Europe (Carneiro et al, 2014). In spite of the large differences in time and geographical origin, in both species we find a radiant development of breeds with changes in behaviour, size, pigmentation, as well as skull and ear shapes.…”
Section: Introductionmentioning
confidence: 84%
“…Therefore, contrary to what has been often advocated (Pai et al, 2015), recent evolution may have been mediated to a larger extent by changes in potentially deleterious changes in amino acid sequence than by regulatory motifs. Certainly, this does not preclude that regulatory changes are important in domestication (Carneiro et al, 2014), but rather hints that its global effect, weighed by frequency, could be no higher than those of deleterious protein sequence changes. Certainly, this is a hypothesis that needs to be verified with larger data sets and more detailed analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Unsurprisingly, some of the most salient features modified by human intervention in several animal species include coat color and behavior, for example, increased tameness and lack of fear towards humans. Domestic animals are also characterized by modified feeding habits, growth or reproductive features, such as the loss of estrus seasonality in ruminants (sheep, cattle and goat) as well as in pigs or rabbits (Chemineau et al, 2008;Carneiro et al, 2014). For instance, in terms of feeding, it was recently found that increased starch digestion capacity has occurred in dogs as compared with wolves, and that although one gene was convincingly identified (AMY2B), other unknown genes are certainly involved (Axelsson et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation